Pengaruh Aplikasi Neuromuscular Taping (Nmt) Terhadap Peningkatan Lingkup Gerak Sendi Lumbal Pada Kasus Keterbatasan Fleksi Lumbal Mahasiswa Fisioterapi Di Universitas Muhammadiyah Surakarta - Shafitri, Yuli Eka; , Umi Budi Rahayu,S.Fis, M.Kes (2017)
Background: Static position and the position of the body causing prolonged suppression and abnormal spinal muscles will affect the lumbar region. Muscle imbalance in the region muscles, while the postural muscles such as m. iliocostalis,m. erector spine too much work your muscles into tigheness. This imbalance affects body movement mainly because of the flexibility of lumbar flexion movement around the lumbar muscles is reduced. Objective: To determine the effect of neuromuscular taping (NMT) to increase lumbar flexion range of motion in the case of limited range of motion in the lumbar flexion physiotherapy student at Muhammadiyah University of Surakarta. Method: This research conducted is quasi experimental by using pre and post test with control design group. Sampling was done by purposive sampling, survey respondents obtained as many as 28 people were divided into two groups. Analysis of data using Wilcoxon Test and Mann Whitney Test. Results: The test results influence the range of motion lumbar flexion between the trearment groups was obtained p-value 0,012 then there is the influence of applications neuromuscular taping (NMT) to increase the range of motion lumbar flexion and the control group was obtained p-value 0,123 then there is no effect. While the influence of different test between the treatment and control groups was obtained p-value 0.002 so that it can be concluded there is a difference of giving application neuromuscular taping (NMT) to increase the range of motion of lumbar flexion. Conclusion: There was am effect Neuromuscular Taping to increased lumbar flexion range of motion in the case of lumbar flexion limitations physiotherapy student at Muhammadiyah University of Surakarta. Keyword: Neuromuscular Taping (NMT), range of motion, lumbar flexion.